A history of modern South Asia politics, states, diasporas - Talbot, Ian (Yale University Press, 2016)
This text explores the region's colonial and postcolonial past, and the cultural and economic Indian reaction to the years of British authority, thus viewing the transformation of modern South Asia through the lens of a wider world.